ANALYZING ENGLISH TEACHERS’ CHALLENGES IN DEALING WITH STUDENTS’ AFFECTIVE COMPETENCE - Yahya Anugrah; Ardiana; Nunung Anugrawati (English Language Teaching Methodology, 2022)
Analyzing the Challenges of English Teachers in Facing Students' Affective Competencies at SMA 1 Muhammadiyah Makassar Thesis Department of English, Faculty of Teacher Training and Education, University of Muhammadiyah Makassar. Supervised by Nunung Anugrawati and Ardiana. This study was conducted to determine the purpose of the study, namely to describe Challenges of English Teachers in Facing Students' Affective Competencies at SMA 1 Muhammadiyah Makassar. The subjects in this study were teachers of SMA 1 Muhammadiyah Makassar. The purpose of this study is to find out what challenges are faced by English teachers in dealing with students' affective competence. The instruments used to collect data are observation, interviews, and documentation. Data analysis in this study is Analysis (QDA), Data Reduction, and Data Display.The results showed that the challenges of the English teacher in dealing with students' affective competence consisted of two factors, namely internal factors and external factors. The strategy used by the English teacher in dealing with students' infective competence is to make learning methods, namely the discussion method and the game method.